TRUST IN WEBSITE AND ITS EFFECT ON PURCHASE INTENTION FOR YOUNG CONSUMERS ON C2C E-COMMERCE BUSINESS - Hendrawan, Dimas; Zorigoo, Khoszaya (Jurnal Aplikasi Manajemen, 2019)
This study aims to determine whether trust in websites in C2C e-commerce businessinfluences purchase intention for young consumers in Indonesia. This explanatory study involved 100 young consumers as respondents as primary data sources supported by secondary data. Primary data was collected through survey questionnaires with purposive sampling technique. Hypothesis testing is done by multiple regression analysis with the help of SPSS 23. The results of this study indicate that there is a significant influence between integrity on purchase intention for young consumers. Other research results also show that ability and benevolence, each of which has a significant influence that encourages the creation of purchase intention for young consumers in the C2C ecommerce business in Indonesia.